2014
DOI: 10.1371/journal.pone.0097267
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Tuberculosis in Northern Viet Nam: A Review of 103 Cases

Abstract: BackgroundChildhood tuberculosis causes significant morbidity and mortality in Southeast Asia, yet little is known about the epidemiology and clinical characteristics of this disease in Viet Nam.ObjectivesTo determine the demographics, clinical presentations, radiographic and microbiologic findings, treatment regimens, and outcomes of children admitted with tuberculosis (TB) to a national referral hospital in Viet Nam.MethodsWe conducted a retrospective case series study of children ≤ 15 years old with bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
2
21
0
1
Order By: Relevance
“…In an individual patient data meta-analysis of over 100 000 children from all over the world, including Peru, Routine registers from primary care clinics do not include recording of paediatric contacts diagnosed with TB in referral hospitals. Furthermore, ruling out TB in young children, especially in those <2 years oldthe age group at highest risk of developing TB after exposure [12,13] involves recognition of warning signs and symptoms by parents and physicians, including the revision of growth charts [10,14] These are not routinely recorded in TB contact investigation, hampering follow-up. Training primary care staff on paediatric TB screening and diagnosis, strengthening communication between referral and primary care facilities, and designing forms to facilitate the appropriate recording and follow-up of contacts may increase TB detection in and provision of preventive treatment to eligible contacts [15][16][17][18][19] Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In an individual patient data meta-analysis of over 100 000 children from all over the world, including Peru, Routine registers from primary care clinics do not include recording of paediatric contacts diagnosed with TB in referral hospitals. Furthermore, ruling out TB in young children, especially in those <2 years oldthe age group at highest risk of developing TB after exposure [12,13] involves recognition of warning signs and symptoms by parents and physicians, including the revision of growth charts [10,14] These are not routinely recorded in TB contact investigation, hampering follow-up. Training primary care staff on paediatric TB screening and diagnosis, strengthening communication between referral and primary care facilities, and designing forms to facilitate the appropriate recording and follow-up of contacts may increase TB detection in and provision of preventive treatment to eligible contacts [15][16][17][18][19] Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this study, other studies have shown that males are often at a higher risk of Tuberculosis and also more likely to die from TB especially in the older age groups. [11][12][13] Mayank et al [12] in India reported a male: female ratio of 1.8:1 among children less than 8years. Also, Blount et al reported a higher male prevalence among males in a Vietnam study [13].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Mayank et al [12] in India reported a male: female ratio of 1.8:1 among children less than 8years. Also, Blount et al reported a higher male prevalence among males in a Vietnam study [13]. However, the genetic risk in males for TB is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This is well below the estimated global average of 10%. Of 103 children (<15 years) diagnosed with tuberculosis in Northern Viet Nam, most were in the 5-14 year age range [54], suggesting gross under-detection in young children who are known to be most vulnerable [55]. Following a successful proof-ofconcept study in 4 provinces [48], the Viet Nam National Tuberculosis Control Program plans to expand community-based contact screening and provision of preventive therapy to all provinces by 2020.…”
Section: Tuberculosismentioning
confidence: 99%